Sintesis Fenetil (O-asetil-p-kumaroil) dari Asam p-kumarat melalui Asetilasi, Klorinasi dan Esterifikasi dengan Fenetilalkohol - Bahja, Bahja; Firdaus, Firdaus; Soekamto, Nunuk H. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2016)
Synthesis of phenethyl (O-acetyl-p-coumaroyl) (4) from p-coumaric acid (1) using phenethylalcohol was succesfully conducted via acetylation (2), chlorination (3), and esterification (4). The acetylation was performed using acetic anhydride in pyridine at room temperature for 6 hours, the chlorination was performed using thionyl chloride in dry benzene by reflux at 75oC for 4 hours, continued with esterification by in situ using phenethylalcohol in dry dichloromethane at room temperature for 4 hours. The structure of each step reaction product was identiï¬ed using FT-IR spectroscopy. The compound 2 was obtained as yellowish crystal with m.p 201-203oC and the compound 4 was obtained as white crystal with m.p 68-69oC.